Intrathyroidal parathyroid cyst presenting with recurrent kidney stones: A case report - Thao, Do Thu; Huong, Nguyen Thi Thanh (Tạp chí Nghiên cứu Y học, 2024)
Parathyroid cysts are rare and can be the cause of persistent hypercalcemia leading to kidney stones. The aim of this article is to present a case presenting to the hospital with recurrent kidney stones and incidentally found hypercalcemia. From there, we discovered a cystic lesion in the thyroid gland. Combining ultrasound and cyst fluid aspiration to measure the concentration of parathyroid hormone in the fluid helped us confirm that the cystic lesion belonged to the parathyroid gland. The patient underwent surgery to remove the cyst and the blood calcium and parathyroid hormone levels returned to normal after surgery.